2021
DOI: 10.1021/acs.accounts.1c00500
|View full text |Cite
|
Sign up to set email alerts
|

Developing Biodegradable Lipid Nanoparticles for Intracellular mRNA Delivery and Genome Editing

Abstract: Conspectus Since the U.S. Food and Drug Administration (FDA) granted emergency use authorization for two mRNA vaccines against SARS-CoV-2, mRNA-based technology has attracted broad attention from the scientific community to investors. When delivered intracellularly, mRNA has the ability to produce various therapeutic proteins, enabling the treatment of a variety of illnesses, including but not limited to infectious diseases, cancers, and genetic diseases. Accordingly, mRNA holds significant therapeutic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 53 publications
0
57
1
Order By: Relevance
“…In addition to other studies, the studies published by our laboratory have demonstrated that the combinatorial library of LNPs can be used for the delivery of nucleic acids, proteins, and small molecule drugs, for a variety of applications in gene silencing, genome editing, cell engineering and tissue regeneration, cancer therapy, antimicrobial applications, and many others 38 , 85 , 121 , 122 , 123 . Nonetheless, challenges still exist in the successful clinical translation of these new drug formulations.…”
Section: Challenges and Future Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to other studies, the studies published by our laboratory have demonstrated that the combinatorial library of LNPs can be used for the delivery of nucleic acids, proteins, and small molecule drugs, for a variety of applications in gene silencing, genome editing, cell engineering and tissue regeneration, cancer therapy, antimicrobial applications, and many others 38 , 85 , 121 , 122 , 123 . Nonetheless, challenges still exist in the successful clinical translation of these new drug formulations.…”
Section: Challenges and Future Studiesmentioning
confidence: 94%
“…This study was significant because it firstly showed that LNP-mediated CRISRP/Cas9 mRNA delivery can induce sufficient and long-term hepatic Angptl3 knockout in mouse model without evident side-effects. We expect that our bioreducible LNPs will advance the systemic delivery of CRISPR/Cas9 genome editing therapeutics for the treatment of hyperlipidemia and other types of liver-associated diseases and disorders 38 , 39 .…”
Section: Lnps For the Delivery Of Nucleic Acidsmentioning
confidence: 99%
“…For targeted delivery, scientists have observed that the targeting functionalities of LNPs are largely related to the chemical structure of the active lipids [ 98 ]. For instance, imidazole-based LNPs preferentially target splenic T cells [ 99 ]; Zukancic et al found that PEGylation is critical for achieving selective organ targeting, even though it is at the lowest ratio in LNPs [ 100 ]. For immunogenicity, Hassett et al found that the particle size may influence LNP immunogenicity; they demonstrated that LNPs at a smaller diameter were substantially less immunogenic in mice, but all the particle sizes tested induced a robust immune response in nonhuman primates (NHPs), suggesting that an optimal mRNA vaccine particle size as determined for rodents may not translate to primates [ 101 ].…”
Section: The Nonviral Nanodelivery Systems Of Mrna Vaccinesmentioning
confidence: 99%
“…In 1995, one of the first nanomedicine doxorubicin liposomal medication, Doxil, was approved for Kaposi's sarcoma; since then, many materialcomposite drugs have been approved by the US Food and Drug Administration (FDA). [2][3][4] Drug delivery systems (DDSs) have realized degradable biological macromolecular drug payload, targeted delivery, controllable release, and favourable pharmacokinetics of drugs. [5][6][7][8][9] Therefore, DDSs have the ability to improve vaccination.…”
Section: Introductionmentioning
confidence: 99%